Pemanfaatan Limbah Kardus untuk Budidaya Jamur Tiram Gantung Vertikal dan Pemasaran Digital dalam Mengoptimalkan Pertanian Berkelanjutan - Setyoningsih Wibowo; Reni Rakhmawati (CV. Global Cendekia Inti, 2026)
The community service initiative, employing a community-based empowerment scheme, was conducted in Semarang City, specifically within the West Semarang District, Salaman Mloyo Village, RT. 01 RW. 02, in collaboration with the Sedekah Ibu waste-sorting community group. The partner's priority challenge is the lack of knowledge regarding the utilization of cardboard waste as a growing medium for oyster mushrooms using an easy and practical vertical hanging model to maximize limited space, integrated with digital marketing to optimize sustainable agriculture. The implementation methods included activity socialization, training execution, and program evaluation. The Community Partnership Program aims to enhance economically productive communities, transforming them into resilient entrepreneurs, and to develop an economically independent community group through cardboard waste utilization. This is achieved through training on processing cardboard waste into an oyster mushroom growing medium using a vertical hanging model, combined with digital marketing to optimize sustainable agriculture. The evaluation of training participants was conducted via a pre-test and a post-test. The highest percentage increase was observed in question item A.5 (56.25%), while the lowest percentage increase occurred in question item C.2 (18.75%).